Corruption in Africa : causes, consequences, and cleanups - Mbaku, John Mukum, 1950- (Lanham, MD : Lexington Books, 2007)
"Corruption in Africa makes a significant contribution to the study of the impacts and eradication of corruption in African societies. John Mukum Mbaku offers a comprehensive analysis of the causes of public malfeasance in African countries and provides a number of practical and effective policy options for positive change. Mbaku demonstrates the destructive relationship between corruption and the abrogation of economic freedoms and entrepreneurship, a system that has clearly left Africa as one of the most deprived regions in the world. Utilizing the tools of public choice theory, the author emphasizes the important role that institutions have in corruption control and recommends reconstructive democratic constitutions as the most effective means of development."--Jacket.
General introduction -- Bureaucratic and political corruption : definitions and measurement -- Corruption in Africa: an overview of causes and country experiences -- The impact of corruption on the African economies -- The international dimension of corruption -- Corruption cleanups in Africa : traditional approaches -- Corruption cleanups in Africa : lessons from public choice theory -- Corruption cleanups in Africa : the role of institutions -- Corruption cleanups in Africa : public financial management -- Corporate governance and corruption -- Corruption cleanups in Africa : a critique of advice from institutional experts -- Democratic constitution making and state reconstruction in Africa : challenges and prospects.
Includes bibliographical references and index.
Keywords: Political corruption -- Africa; Corruption -- Africa; Corruption (Politique) -- Afrique; Corruption -- Afrique; Corruption; Political corruption; Africa